An algorithm for the selection of antiarrhythmic drugs for clinical pharmacologist - A. A. Upnitskiy (Медицинский совет, 2014)
The choice of antiarrhythmic drugs (AAD) should be based on a certain algorithm comprising at its first stage selection of effective drugs (if applicable), at the second stage - exclusion from the list of the selected drugs those which may be dangerous taking into account also the associated pathologies and physiological conditions of the patient, and at the third stage - "personalization" of AAD (mode of administration, frequency, duration, timing and criteria for the evaluation of both efficiency and safety of AAD). The article describes the algorithm for the selection of antiarrhythmic drugs.